How does perceived respect affect innovative behavior? The role of thriving at work and spiritual leadership - Zhao, Li; Liu, Pingqing; Zhang, Fan; Xu, Shuang; Liu, Yuanyuan (Frontiers in Psychology, 2022)
Many enterprises use innovation to deal with the rapidly changing business environment and gain market competitiveness. How to internally motivate employees, especially the new generation of employees（e.g. ,employees born after 1980）, to take initiative to innovate is receiving great interest from both academic and practical perspectives. Based on the broaden-and-build theory, this study presents a moderated mediation model of the impact of perceived respect on innovative behavior. SPSS and Mplus were used to analyze the data from 506 leader–employee pairs. The results show that perceived respect had a significant positive influence on innovative behavior through the effect of thriving at work, and the moderating effect of spiritual leadership was significant. When the effect of spiritual leadership was strong, the effect of perceived respect on innovative behavior through the effect of thriving at work was enhanced. This study reveals the dynamic mechanisms of improving employees’ innovative behavior, providing theoretical and practical ideas for promoting enterprises’ sustainable and innovative development.